تقدير دالة الاستهلاك تحت فرضية الدخل الدائم: حالة ليبيا - الحوتة , أحمد على (Scientific Journal of University of Benghazi, 2021)
The study attempts to estimate the consumption function in the Libyan economy under the permanent income hypothesis for the period between 1970-2012 using Cogan's Adaptive Expectations Model. Empirical results have shown a limited level of support for the permanent income hypothesis. Moreover, the study showed that past consumption affects current consumption. This result is consistent with the relative income hypothesis.